Influence of pyridinic nitrogen on tautomeric shifts and charge transport in single molecule keto enol equilibria - G. R. Berdiyorov (Scientific Reports)
Abstract Keto-enol tautomerism in organic molecules presents a potential for modulating the charge transport at the nanoscale. The reduction of the isomerization barrier and favoring the highly conductive enol form are the main challenges towards practical implementation of this phenomenon. Using density functional theory calculations, we have demonstrated that pyridinic nitrogen in biphenyl molecules with keto-enol tautomerism can successfully make the conductive enol form energetically more favorable. This enhanced stability originates from the hydrogen bonding between the pyridinic nitrogen and the hydroxyl group in the enol state. The presence of the pyridinic unit further enhances the conductance of the enol form while reducing that of the keto form compared to the pristine molecule. The novelty of our findings lies in the use of pyridinic nitrogen to control isomerization through hydrogen bonding, offering a new approach to tuning electronic properties for molecular devices. These findings can be valuable in the development of functional molecular devices based on the keto-enol isomerization phenomenon.